Post-fire behaviour of circular recycled aggregate concrete-filled stainless steel tube stub columns - Lum, Candice Hui Mei (Nanyang Technological University, 2024)
An experimental study of post-fire circular recycled aggregate concrete-filled stainless steel tube (RACFSST) stub columns is presented in this report. Twelve stub columns were manufactured using three replacement ratios of recycled coarse aggregates (70%, 35%, and 0%). Firstly, specimens were heated for 45 minutes, 30 minutes, 15 minutes, and 0 minutes, according to ISO-834 fire curve. Stub column tests were then carried out together with material tests, comprising concrete cylinder tests and post-fire coupon tests. Results were analysed in detail, including ultimate loads, end shortening curves, confinement effects, and initial compressive stiffnesses. Subsequently, the experimental data were used for assessment of design codes. Since stainless steel–recycled aggregate concrete composite structures are not covered by current design codes, relevant codes regarding circular carbon steel tube stub column filled with natural aggregate concrete at ambient temperature, as established in Europe, Australia/New Zealand and America, was evaluated using post-fire material properties. Based on the assessment, both the Australian/New Zealand and European codes achieved acceptable design accuracy, while the American specification offered conservative and scattered post-fire cross-section resistance predictions.